University students’ awareness of eco-friendly technology and reception of digital short messages - Aldawsari, Norah D.; Abdellatif, Mohamed Sayed; Ibrahim, Ashraf Ragab; Abdelhafez, Ahmed M. (Research Journal in Advanced Humanities, 2026)
Universities are increasingly expected to advance sustainability awareness. Yet little is known about how students in Saudi higher education receive short eco-friendly technology messages distributed through campus digital channels. This mixed-method descriptive study also empirically examined student eco-tech micro-message exposure and further tested student eco-tech micro-message reception (attention, comprehension, cultural salience, design appeal, credibility, and perceived impact). Three hundred and twenty‐six students (180 males, 146 females) filled out a questionnaire. Cross-channel exposure was low and awareness as well as the general eco-awareness was high. Positive relation between message exposure and total awareness (r =. 36, p <. 01) and with all three aspects of response/awareness (r =. 19–. 34). A gender difference was only found for exposure, rated higher by males (d = 0.33), and not for recognition. The qualitative track (about 120 relevant answers) found that students are mostly fans of social media and messaging apps (especially WhatsApp), because they are habitual and instantaneous. 71 Successful messages were brief, actionable, and culturally relevant often involving moral–religious framing and simple analogies. Some students suggested clearer sourcing, stronger connections to Vision 2030, specific examples of what could be implemented on campus and cleaner visual design.